Analysis of heart retransplantation outcomes in the new donor heart allocation system. (April 2023) - Rempakos, Athanasios; Doulamis, Ilias P.; Papamichail, Adamantia; Tzani, Aspasia; Briasoulis, Alexandros
Cardiac graft failure may require repeat heart transplantation (HTx). Outcomes of patients that undergo repeat HTx have not been well described. We compared patients that received repeat HTx with patients that received initial HTx by inquiring the United Network for Organ Sharing (UNOS) database between 2015 and 2021. The primary endpoint was all-cause mortality, while the role of baseline characteristics was also investigated. Patients were stratified according to whether they received initial HTx (n = 19, 727, 97%) or repeat HTx (n = 578, 3%). Among the study population, 10, 860 (53.5%) patients received a HTx using the old UNOS allocation system, whereas 9445 (46.5%) patients received a HTx after the implementation of the new UNOS donor allocation system in October 2018. In this sub-group of HTx recipients in the new allocation system era, the adjusted 1-year survival of repeat HTx patients remained lower than that of initial HTx patients (hazard ratio (HR): 1.19; 95% confidence interval (CI): 1.15, 3.18; p = 0.013). When we compared the 1-year survival of repeat HTx patients before and after the implementation of the new allocation system, the adjusted 1-year survival was similar between groups (HR: 1.14; 95% CI: 0.71, 1.84; p = 0.591). The unadjusted risk of 30-day mortality was not significantly different in the new vs old allocation system. Mortality associated with repeat HTx remained higher than initial HTx but the new donor allocation system implementation did not affect outcomes.